Examining the Ripple Effect of COVID-19 on Agriculture and Food Security - , Yuvraj Singh; , Tanvir Singh; , Munish Kaundal (Archives of Current Research International, 2025)
The COVID-19 pandemic caused a devastating effect on the world's agricultural and food security system, impacting production, distribution, and consumption patterns. The government's enforcement of a nationwide lockdown resulted in the halting of industries, which negatively impacted the entire supply chain from producers to consumers. This document explores the repercussions of COVID-19 on the Agro-food system and its economic fallout, emphasizing critical components such as food production, demand variations, price surges, security, and the durability of supply chains. Lockdowns, border closures, and labour shortages led to supply chain disruptions, rising costs of production, and losses, especially for smallholder farmers. Impulsive buying and hoarding led to artificial shortages, shifting consumer attention towards non-perishable and locally produced food items. Globalization placed pressures on trade, increased food vulnerability and, as a result, raised food prices and decreased access to essential agricultural inputs. Despite these barriers, the crisis accelerated the widespread adoption of digital technologies in agriculture, including e-commerce, precision agriculture, and automation. Governments created policies to enhance the resilience of the food supply chain, promote sustainable agriculture, and provide local food production. Long-term recovery plans involve investments in climate-smart agriculture, enhanced logistics, and digital infrastructure to enhance economic resilience and food security. The pandemic highlighted the resilient, long-term food systems that could adapt to the requirements of future global emergencies. Furthermore, the crisis unveiled agricultural labour markets, bearing in mind that controls of seasonal and migrant work rendered them less beneficial. Farmers instead accommodated mechanization, automation, and other emerging systems of farming as they tried to offset the lack of labour. Pressure from consumers on food nutritional value and safety led to the demands for local and organic food. Governments and non-governmental bodies collaborated to enhance food distribution systems in a bid to make vital commodities accessible. Supply chain resiliency was a key agenda, and it led to investments in intelligent logistics, e-marketplaces, and improved warehousing. The pandemic also put the spotlight on local production of food and self-sufficiency, and that has created a shift towards sustainable practices such as regenerative agriculture, hydroponics, and urban agriculture. These are articulations of a long-term transformation in world food systems.